2021 IEEE International Conference on Image Processing (ICIP) 2021
DOI: 10.1109/icip42928.2021.9506510
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Based Self-Supervised Learning Monocular Depth Estimation With Edge Refinement

Abstract: Learning depth from a single image extracted from unlabeled videos has been attracting significant attention in the past few years. In this work, we propose a new depth estimation neural network with edge refinement to predict depth. First, we introduce a dual attention module into depth prediction module to integrate global information into local features and improve local features' capability of representation. Second, to increase the details between objects in scenes, we propose a subnetwork to predict edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Zhang et al reported a selfsupervised method in which channel and spatial attentions are embedded at the bottleneck of an encoder-decoder architecture [41]. Similar works include [42,43], in which channel and spatial attention blocks are parallel or sequentially inserted at the bottleneck. The channel and spatial attention modules can also be inserted into any stage of the decoder [44].…”
Section: Self-supervised Trainingmentioning
confidence: 99%
“…Zhang et al reported a selfsupervised method in which channel and spatial attentions are embedded at the bottleneck of an encoder-decoder architecture [41]. Similar works include [42,43], in which channel and spatial attention blocks are parallel or sequentially inserted at the bottleneck. The channel and spatial attention modules can also be inserted into any stage of the decoder [44].…”
Section: Self-supervised Trainingmentioning
confidence: 99%